An extensible, generic environmental process modelling framework with an example for a watershed of a shallow lake. (January 2016) - Varga, M.; Balogh, S.; Csukas, B.
Abstract: We present a modelling framework for the generation of environmental process models. The framework builds on the Direct Computer Mapping method with an editable, process network based expert module and interpreter. The expert interface supports mapping of objects from the GIS layers onto the prototyped state, transition and connection elements of the case specific generic process model. The developed general purpose interpreter generates the standardized declarative facts and clauses, describing the actual model with the locally executable program prototypes. This input is executed by the general kernel. The model interpreter generates also the case specific templates for the (optionally web based) user interface, while map-server utilizes the GIS shape files of expert model. The implementation supports the extension of the model with new components in space and time. The framework is illustrated by an example for the watershed of Lake Balaton. Graphical abstract: Highlights: We map the GIS objects onto an editable net structure, used as an expert interface. We interpret this net structure to uniform declarative facts and clauses. This declarative simulation model is executed by our general purpose kernel program. The interpretation is accompanied by template generation for the user interface. The environmental model can be extended by new elements and components, easily.